The Earth as Body in Old Norse - Mckinnell, John (Religionsvidenskabeligt Tidsskrift, 2022)
ABSTRACT: This article investigates two of three main ways outlined by Snorri Sturlusson in Gylfaginning in which Old Norse poets might refer to the earth in their poetry: By reference to the myth of the killing of Ymir as well as by reference to the immediate family of the goddess Jǫrð. By looking at the meaning of these references to the origins of the earth, the article investigates the underlying human ideas and reactions of these references. RESUME: Denne artikel undersøger to af tre hovedmåder skitseret af Snorri Sturlusson i Gylfaginning, hvorpå norrøne digtere kunne henvise til jorden i deres poesi: Gennem reference til myten om drabet på Ymir såvel som ved reference til gudinden Jǫrð’s nærmeste familie. Ved at se på betydningen af disse henvisninger til jordens oprindelse undersøger artiklen henvisningernes underliggende menneskelige ideer og reaktioner.